2017
DOI: 10.1002/jmri.25785
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo MRI evaluation of prostate cancer: Localization and margin status prediction of prostate cancer in fresh radical prostatectomy specimens

Abstract: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:439-448.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several authors have pursued similar methods in an effort to provide surgeons with accurate perioperative information on the margin status in tumors other than VSCC. Previously, breast, bone, gastric, esophageal, tongue and prostate specimens have been examined by ex vivo MRI. As far as we are aware, employing ex vivo MRI in RLE specimens is new, but other (imaging) techniques such as FSA and optical coherence tomography (OCT) have been investigated as a means to assess the surgical tumor‐free margins.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have pursued similar methods in an effort to provide surgeons with accurate perioperative information on the margin status in tumors other than VSCC. Previously, breast, bone, gastric, esophageal, tongue and prostate specimens have been examined by ex vivo MRI. As far as we are aware, employing ex vivo MRI in RLE specimens is new, but other (imaging) techniques such as FSA and optical coherence tomography (OCT) have been investigated as a means to assess the surgical tumor‐free margins.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Ex vivo 7T MRI of a radical prostatectomy specimen demonstrating a lesion in the left transition zone of the prostate (T) with low signal intensity on T2W sequence concerning for prostate cancer, as well as a BPH nodule (B) and the urethra (U); (b) corresponding H&E stained histopathology slide at 100× magnification with pathologist's annotation of a prostate cancer lesion (T). Previously published in: Heidkamp et al [20]. MRI, magnetic resonance imaging; BPH, benign prostatic hyperplasia.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Durand et al performed ex vivo MRI with direct histological correlation of the prostate gland that approached histological spatial resolution enabling the visualization of gland microanatomy with MRM (21). More recently, a study has investigated the ability of ex vivo 7.0-T MRI to localize prostate cancer and to predict the margin status in fresh radical prostatectomy specimens using histology as the reference standard (22). The author found that ex vivo MRI was able to accurately localize prostate cancer in radical prostatectomy specimens, and the technique provided information on the margin status (22).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a study has investigated the ability of ex vivo 7.0-T MRI to localize prostate cancer and to predict the margin status in fresh radical prostatectomy specimens using histology as the reference standard (22). The author found that ex vivo MRI was able to accurately localize prostate cancer in radical prostatectomy specimens, and the technique provided information on the margin status (22). In brain tumors, Martinez-Bisbal et al combined MRM with MR spectroscopy to study metabolites of ex vivo tumors at high resolution (23).…”
Section: Introductionmentioning
confidence: 99%